PENERAPAN MODEL DISCOVERYLEARNINGMETODE INQUIRYSEBAGAI UPAYA PENINGKATAN PRESTASI BELAJAR EKONOMI DI MA AL-MUJADDADIYYAH MADIUN - Sudjianto Sudjianto (Universitas PGRI Madiun, 2014)
The teacher as the main implementer of learning to understand and master the application of learning models , make changes and to develop teaching skills . Teachers need to pay attention to the model of learning , because learning model is key to ensuring the learning process in the classroom .There are three models of learning are applied to the curriculum in 2013 , namely the Discovery Learning model of learning , problem-based learning model and project -based learning model . The learning model discovery learning stimulation / arousal , statement / problem identification , data collection , data processing , verification / evidence and draw conclusions / generalizations . By applying the method of Discovery Learning , students actively seek and cultivate their own information content of higher mental processes or more banyak.siswa will be active in the learning process because one of the friends group is more aware of the material can explain the material to friends who are not informed about .This research is Classroom Action Research Discovery Learning models by applying the inquiry method . The subjects in this study were students of class XI MA Al - Mujaddadiyyah Madison school year 2013/2014 . The data was collected using the observation sheet to assess learning ability and questionnaire to the data sheet student interest . Analysis of data for learning and student interest using descriptive qualitative analysis , quantitative data by calculating the percentage of first cycle and second cycle .The results showed that the use of methods can improve the ability of Discovery Learning Study abroad and student interest . Improved learning ability of students can be seen from the increasing number of students who are active in the second cycle , Increasing student achievement can be seen from the increasing student mastery learning and getting better value from each of the aspects which include : discussion of the results of expression , receiving the opinion of the right reasons , concerned about the group , tasks and helping friends .